Leveraging SME finance through value chains in the CAREC landlocked economies: The case of the Kyrgyz Republic - Kanat Tilekeyev (Asian Development Bank Institute (ADBI), 2019)
The paper discusses state, regulative framework, and recent developments in leveraging access to finance for micro, small, and medium-sized enterprises (MSMEs) in the Kyrgyz Republic through global value chain (GVC) examples in the Kyrgyz Republic. Access to finance in the Kyrgyz Republic is growing and demonstrates improvement of financial inclusion of companies SME sector in the Kyrgyz Republic as well as the sector of individual entrepreneurs and peasant farmers. Four selected value chains in agriculture, industry and service sector demonstrate the gaps in the access to finance of the MSME entities in the value chains supply to export markets. Some practical recommendations are proposed, aiming to decrease financial gaps for the SME sector in building resilient global value chain supplies.
Keywords: G21; Q14; L26; M21; 330; small and medium-sized enterprises; micro SMEs; global value chains (GVC); financial inclusion; financial institutions; business development; business environment; access to finance; Kyrgyz Republic